2015
DOI: 10.5005/jp-journals-10024-1678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baseplates of Orthodontic Appliances with in situ generated Silver Nanoparticles on Cariogenic Bacteria: A Randomized, Doubleblind Cross-over Clinical Trial

Abstract: Aim Polymethyl-methacrylate (PMMA) is commonly used primarily for baseplates of orthodontic appliances (BOA). The activities of cariogenic bacteria in biofilm on these surfaces may contribute to dental caries, gingival inflammation and periodontal disease. The PMMA incorporated with nanoparticles of silver (NanoAg-I-PMMA) and NanoAg in situ in PMMA (NanoAg-IS-PMMA) have been shown to control the growth of cariogenic bacteria, but clinical trial of anti-cariogenic application of these novel materials in orthodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Four publications use an animal study or clinical trial to obtain the authentic antimicrobial efficiency of silver nanomaterial. 13,[28][29][30] Silver nanoparticles bring forth an antibacterial effect for silver nanomaterials. Although the exact mechanism of silver nanoparticles' antibacterial effects has not been entirely clarified, various antibacterial actions have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four publications use an animal study or clinical trial to obtain the authentic antimicrobial efficiency of silver nanomaterial. 13,[28][29][30] Silver nanoparticles bring forth an antibacterial effect for silver nanomaterials. Although the exact mechanism of silver nanoparticles' antibacterial effects has not been entirely clarified, various antibacterial actions have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies measured bactericidal properties in vitro, whereas only four studies were operated in vivo, including two animal studies and two clinical trials. 13,[28][29][30] The results of the minimum inhibitory concentration and the minimum bactericidal concentration of silver nanomaterials against cariogenic bacteria have high degrees of variation in different studies. [31][32][33] The agar diffusion test demonstrated that disks treated with silver nanomaterials have larger inhibition zones compared with disks treated with water.…”
Section: Effects Of Silver Nanomaterials On Cariogenic Bacteriamentioning
confidence: 99%
“…Although our results might support this possible argument, more studies that determine the effect of AgNPs according to the corrosion level, topographic alterations, roughness, ion release, and other important properties of the most used orthodontic archwires should be investigated. In addition, the AgNPs have also been used for other different applications in the orthodontic field; the results of those investigations demonstrate that the orthodontic appliances with AgNPs have the ability to improve their antibacterial properties in several types of microorganisms involved in the white spots [36][37][38][39]. Our results suggest that the AgNP samples used in this study have the potential to be an excellent antimicrobial alternative with antiadherence properties that might facilitate the prevention of white spots caused by the S. mutans bacteria during the orthodontic therapeutics for the most conventional orthodontic appliances.…”
Section: Discussionmentioning
confidence: 99%
“…Most anti-biofilm based randomized clinical trials have focused on infections associated with biofilm formation on abiotic surfaces: medical devices (especially ventilator-associated pneumonia and catheter-related infections) or dental surfaces. In these randomized clinical trials, the main strategy used to successfully control biofilm formation was the use of surface-coated ( Berra et al, 2008 ; Kollef et al, 2008 ) or surface-treated catheters ( Scannapieco et al, 2009 ; Quintas et al, 2015 ) and/or changes in surface composition of the device ( Ghorbanzadeh et al, 2015 ). The last paragraph of this review will focus on these different strategies, with special emphasis on their advantages and limitations.…”
Section: Successful Use Of Anti-biofilm Methods In Human Healthmentioning
confidence: 99%